2019
DOI: 10.1017/s0954579419000828
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories and Predictors of Children's Early-Starting Conduct Problems: Child, Family, Genetic, and Intervention Effects

Abstract: AbstractSeveral research teams have previously traced patterns of emerging conduct problems (CP) from early or middle childhood. The current study expands on this previous literature by using a genetically-informed, experimental, and long-term longitudinal design to examine trajectories of early-emerging conduct problems and early childhood discriminators of such patterns from the toddler period to adolescence. The sample represents a cohort of 731 toddlers and diverse families… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 79 publications
4
48
2
Order By: Relevance
“…Second, consistent with hypotheses and extant literature, higher levels of harsh parenting, including more overreactive and punitive forms of discipline reported by parents, were related both to more child CP and higher CU traits. Findings are consistent with a large literature on harsh parenting, which exacerbates coercive and negative parent-child interactions, leading to an escalation in non-compliant, aggressive, and disruptive child behavior, further increasing risk for CP and CU traits [ 12 – 15 ]. At the same time, via potentially distinct etiological mechanisms, exposure to harsh discipline can desensitize children who are relatively more fearless to both punishment and the negative consequences of their behavior, thereby increasing risk for CU traits [ 22 , 23 , 71 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Second, consistent with hypotheses and extant literature, higher levels of harsh parenting, including more overreactive and punitive forms of discipline reported by parents, were related both to more child CP and higher CU traits. Findings are consistent with a large literature on harsh parenting, which exacerbates coercive and negative parent-child interactions, leading to an escalation in non-compliant, aggressive, and disruptive child behavior, further increasing risk for CP and CU traits [ 12 – 15 ]. At the same time, via potentially distinct etiological mechanisms, exposure to harsh discipline can desensitize children who are relatively more fearless to both punishment and the negative consequences of their behavior, thereby increasing risk for CU traits [ 22 , 23 , 71 ].…”
Section: Discussionsupporting
confidence: 88%
“…CU traits were added to the DSM-5 as a specifier for the diagnosis of conduct disorder [ 9 ], emphasizing the importance of understanding the etiology of CU traits to inform personalized treatments for CP [ 10 ]. Despite genetic influences on CP [ 11 ], multiple aspects of caregiving inadvertently socialize children to become aggressive, non-compliant, or violent [ 12 , 13 ]. In particular, harsh and intrusive parenting contribute to cycles of coercive parent-child interactions [ 14 , 15 ], whereas positive reinforcement (e.g., contingent use of praise) and proactive parenting practices (e.g., scaffolding) predict reductions in childhood CP [ 16 , 17 ]…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have shown influences on component features of disruptive behavior and self-regulation, suggesting that parsing is possible. For example, the FCU has demonstrated intervention effects on externalizing behaviors (e.g., Dishion et al, 2008; Shelleby, Shaw, Dishion, Wilson, & Gardner, 2018; Smith et al, 2014) and inhibitory control in early childhood (Lunkenheimer et al, 2008), self-regulation from early childhood into school age (Chang, Shaw, Dishion, Gardner, & Wilson, 2014; Shelleby et al, 2012), and ODD symptoms in school-age children and adolescence (e.g., Dishion et al, 2014; Shaw et al, in press; Shaw et al, 2016; Shelleby et al, 2018; Smith et al, 2014). Additionally, the FCU has demonstrated direct and indirect effects on internalizing problems in school-age children after intervening in early childhood (Lemery-Chalfant, Clifford, Dishion, Shaw, & Wilson, 2018; Reuben, Shaw, Brennan, Dishion, & Wilson, 2015).…”
Section: Can Interventions Improve Irritability?mentioning
confidence: 99%
“…A few years later, he agreed to adapt the FCU to another developmental period of biological and social transition, the “terrible twos” (Dishion et al, 2008; Shaw, Dishion, Supplee, Gardner, & Arnds, 2006), and locate the service at a federally funded agency for families with young children at economic disadvantage: Women, Infants, and Children Nutritional Supplement Centers, making it possible to scale up the intervention nationally without having to create a new mechanism for the FCU's delivery. Ample empirical validation for the adolescent and early childhood versions of the FCU is evident, with follow-up outcomes extending more than 10 years for both versions (Connell, McKillop, & Dishion, 2016; Shaw et al, 2019).…”
Section: Intervention Development and The Family Check-upmentioning
confidence: 99%